Discretion as to the Object of the Criminal Law of Corruption in Indonesia - Yendra Tamin, Boy; ., . (International Journal of Engineering and Technology, 2018)
The high number of corruption cases among government officials in Indonesia cannot be separated from what is the object of the criminal law of corruption, especially since corruption laws in Indonesia do not distinguish between discretion and abuse of authority due to position. This raises the question, can discretion be the legal object of criminal corruption? This legal research is carried out with conceptual approach, statute approach and case approach, it can be concluded that discretion cannot be used as an object of the criminal law of corruption because discretion is not based on the principle of legality. Placing discretion as the object of the law of corruption is inconsistent with the demands of the welfare state. In the use of discretion, it is necessary only to set strict standards and supervision, and the use of discretion with consistent purpose principles. And it must be stated in the Act, that the expression is not the object of corruption.Â Â